PENGEMBANGAN DAN VALIDASI TES VIRTUAL BERPIKIR TINGKAT TINGGI (LEVEL ANALISIS) PADA MATERI ASAM BASA - Karolina, Ani (2016)
Penelitianinibertujuanuntukmendapatkantes virtual yang valid danreliabeluntukmengukurkemampuanberpikirtingkattinggisiswapadamateriasambasa.Metode yang digunakandalampenelitianiniadalahmetodepengembangandanvalidasiuntukmengetahuikualitastes yang dikembangkan (ujivaliditaskontendanreliabilitas).Respondendalampenelitianiniadalah 175 orang siswakelas XI MIA dan 3 orang guru kimia di SMA Negeri yang ada di Cianjur. Hasildaripenelitianiniyaitu: (1) validitaskontentes virtual diujidengan CVR (29 soal valid) dan CVI yang dihasilkanadalah 0,97, ituartinyabutirsoalpilihangandainibaiksekali;(2) reliabilitastesvirtual ditunjukkandenganCronbach's alphadanCronbach's alphauntuksemuabutirsoalpilihangandaadalah 0,784 dimanaukurankeajegandapatditerima; (3) Tes virtual asambasamemilikidayapembedasebesar 0,40 dengankategoribaikdantingkatkesukaransebesar 0,48 dengankategorisedang; (4) guru-guru dansiswamemberikanresponpositifterhadaptes virtual berpikirtingkattinggipadamateriasambasa yang dikembangkandilihatdarisegikemudahanpenggunaantes virtual, penggunaanmultimedia yang terdapatpadasoal, manfaat, danwaktupengerjaantes.;-- This research aims to obtain a valid and reliable virtual test to measure student's higher order thinking skill of acid-base. The method in this research is development and validation method to known the quality of the test developed (content validity testing and reliability testing). Respondents in this research are 175 of 11thofscience students and 3 chemistry teachers in Public Senior High School in Cianjur. The results of this research are: (1) Validity content of this virtual test examined by CVR (29 items which are valid), and the result of CVI is 0.97, it means this virtual test has content validity in accordance with the criteria; (2) reliability of virtual test is indicated by Cronbach's alpha and the Cronbach's alpha for all multiple choice items is 0.784 it means this virtual test has reliability in accordance with the criteria; (3) virtual test of acid-base items has distinguishing ability of 0.40, that is indicated good category and level of difficulty of 0.48, that is indicated medium category; (4) The virtual test of higher-order thinking on acid base material which is developed got good and positive responses from teachers and students in terms of ease to use the virtual test, to use multy media that have involved into the questions, advantages and processing time